ORHUN ABİDELERİ'Nİ OKUMA ÇALIŞMALARINDAKİ FARKLILIKLAR - HOROZ, MEHMET (Fırat Üniveristesi, 1996)
The funerary inscription, of Orfchon is early samples TurKish Languages. The funerary inscription of Orkhon is three diffrent stone: "Those are: (1) the funerary inscnption of Kül Tigin in A.D. 732, cited as As I followed by the side (E, W, N, S) of the stone and the line ontiie side mt!» our reaserchaM shownKT, (2) the funerary of Bilge Kagan composed in A.D. 73, cited as simflary BK in me our reaserch. (3) the funerary inscription of Tonyutofc as T cited in thesour reaserch (study). The funerary inscription of Or&fcoa had read very explerir. Our first purpose of this study have been fourd the diffemt read and semantic of the Orfchon Inscription and My second purpose has ken to establish tha original meaning of all minis in the dictionary. ! have tsJam that the dictionary of Clauson and as cüed SGC to this study. There are the porblem of transcribing early texts. My fust purpose have been to showed me hecuhMtyof the OrUhon Inscription Alphabets, fonetfc and gramitfc. This person I have given in the sudy the peculiarity alphabet?, fonetic and grametic of the orKhon Inscription. For the shown the different read and semantic the Orfehon Inscrq?tion timt I have «ten the basic text the text of Thomsen. And I have showned the text of Thomsen with YT1, VT3, and VT3 sips. And after, I have showned me marginal not of this text me others reads of the Orfehon Inscription of the other explorer.390 For the semantic of the word in to Orkhon Inscription, I have taken An Ethnological Dictionary Pre TTiirteent- Century Turkis of Sir Gerard Ckuson in tnis study. After shorn the different read and semantic I have explained the causes of the deffemt read and semantic. My basic purpose in tins study have been showed ihe different of the read and semantic and have been helped for the best read and semantic of the word and structure in the Or&hon Inscription with this study. /
The Different of read studies of the Orhun Inscription
Keywords: Tarih; History